Nuclear envelope tethering of the genome modulates cohesin loop extrusion - Shan, Fengnian; Zhao, Han; Qin, Shiyi; Lin, En; Xia, Sijian; Lin, Yinzhi; Lyu, Fangxuan; Pei, Chongren; Liu, Fuhai; Guo, Qiao; Li, Siyu; Shu, Lirong; et al. (LangTaoSha Preprint Server, 2026)
The nuclear envelope (NE) plays a crucial role in genome organization by tethering heterochromatin to the nuclear periphery. Yet, how individual NE-associating factors regulate 3D genome architecture remains incompletely understood. Here, we leverage the mitosis-to-G1 phase transition as an experimental system to dissect the roles of Lamin A/C and Lamin B receptor (LBR) in post-mitotic genome refolding. Loss of LBR but not Lamin A/C triggers profound architectural aberrations, including enhanced self-interaction of lamina-associating domains (LADs) and a concomitant decrease in local intra-loop contacts. Although LBR rapidly re-associates with chromatin in early-G1, its structural impacts manifest only in late-G1, suggesting a temporal decoupling between chromatin binding and architectural function. Mechanistically, we demonstrate that such aberrations are not driven by altered heterochromatin self-attraction, but instead reflect the relief of a biophysical constraint imposed by LBR on cohesin-mediated loop extrusion. In support of this, reducing cohesin occupancy via Nipbl degradation mitigates the architectural impacts of LBR loss, while selective mapping of cohesin contacts reveals that LBR depletion directly increases cohesin extrusion processivity. Moving beyond an LBR-centric view, we extend these findings through an inducible synthetic tethering system and polymer simulations to establish a universal NE-mechanical tethering framework. In this framework, the NE regulates cohesin loop extrusion in a tethering-mode-specific manner: while bulk chromatin anchorage imposes a mechanical constraint that restricts cohesin processivity, focal tethering of CTCF-binding sites (CBS) facilitates loop formation. Our study establishes the NE as a general mechanical governor of the genome that regulates 3D chromatin architecture by modulating cohesin extrusion capacity.